IPO valuation using the price-multiple methods: evidence from Malaysia. Issue 4 (1st February 2021) - Ong, Chui Zi; Mohd-Rashid, Rasidah; Taufil-Mohd, Kamarun Nisham
Abstract : Purpose: This study aims to investigate the valuation accuracy of Malaysian initial public offerings (IPOs) by using price-multiple methods. Design/methodology/approach: Cross-sectional data including 467 IPOs listed on the Malaysian stock exchange were used for the period of 2000–2017. This study used univariate ordinary least square (OLS) regression to analyse the relationship between IPOs' price-multiples and comparable firms' price-multiples. The test of valuation accuracy was conducted via computing valuation errors by segregating the sample into two groups: fixed-price IPOs and book-built IPOs. Furthermore, multiple OLS regression was used to examine the influence of IPO valuation on underpricing. Findings: The findings of the results suggested that IPOs price-to-earnings (P/E), price-to-book (P/B) and price-to-sales (P/S) multiples were positively related to the median P/E, P/B and P/S multiples of five comparable firms matched by industry and revenues. The P/S multiple was shown to be the most significant valuation method, specifically in book-built IPOs. The findings indicated that those firms that had a lower valuation in comparison to the comparable firms were inclined to underprice their IPOs to allure investors to subscribe IPOs. In addition, book-built IPOs that had fair valuations were inclined to generate higher initial returns for investors. Practical implications: The findings of this study observed implications for underwriters in avoiding the mis-valuation issue by considering the book-building mechanism. Originality/value: This study attempted to explore the suitability of the valuation method to value IPOs in Malaysia.